Appraisal of caesarean section incidence and indications at manipal teaching hospital, Pokhara, Nepal - Shrestha, Aashika; Shrestha, Junu; Gurung, Sangeeta Devi (Asian Journal of Medical Sciences, 2021)
Background: Worldwide lower segment caesarean section (LSCS) is the most commonly performed obstetric operation. Though it’s a lifesaving procedure it is sometime associated with both short and long term risk which can extend many years beyond current delivery and affect health of mother, fetus and future pregnancy. Aims and Objective: The study aims to examine the incidence and indication of caesarean section at Manipal teaching hospital. Materials and Methods: A retrospective descriptive study of 2140 cases was carried out at a teaching hospital in Pokhara, Nepal. Data regarding total number of vaginal delivery and caesarean section performed in 1 year duration from August 2019 to July 2020 was obtained from the operation record book and medical record section of hospital. Other information regarding age, parity, gestational period and indication of cesarean section were obtained and depicted in tabulated form. The collected secondary data has been analyzed employing frequencies and percentage. Results: During the one year study period, 2140 deliveries were made out of which 1170 (54.7%) cases underwent caesarean section. Out of those cases 78.8% of women underwent emergency LSCS. Most of the women were in the age group of 21-30 years (69.2%). In 81.2% cases caesarean was done between 38-42 weeks gestation. 52.3% of cases were multigravida, 43.8% were primigravida and only 3.1% were grand multigravida. Most common indication of caesarean were fetal distress (23.7%), previous LSCS (23%), cephalopelvic disproportion (15.6%), oligohydramnios (11%) followed by breech, preeclampsia, eclampsia and non-progress of labour. Conclusion: This study revealed that the incidence of caesarean section was high in the hospital and majority of the patients who underwent caesarean section had an emergency caesarean section. The commonest indications were fetal distress and repeat cesarean section. The issue requires further investigation to identify reasons for high CS rate and raises necessity of policy guidelines and intervention in order to prevent possible unjustified use of surgical delivery.